В строю крылатых: из воспоминаний / Ф. Я. Фалалеев - Фалалеев Федор Яковлевич (Удмуртия, 1978)
Экземпляры: Кр () / Инвентарный номер: 37697 / Сис.шифр: 63.3(2)622(2Рос=Удм) / Авт.знак: Ф 19 / ГРНТИ: 03.23.55 / ББК: 63.3(2)622(2Рос=Удм)